2002
DOI: 10.1016/s0014-5793(02)03142-3
|View full text |Cite
|
Sign up to set email alerts
|

Only the soluble form of the scavenger receptor CD163 acts inhibitory on phorbol ester‐activated T‐lymphocytes, whereas membrane‐bound protein has no effect

Abstract: The extracellular moiety of the hemoglobin/haptoglobin scavenger receptor CD163 (RM3/1 antigen) can be shed from monocytes and is a normal plasma component. We found that in a dose-dependent manner soluble CD163 induces a decrease in CD69 expression, a reduced [ 3 H]thymidine uptake and a down-regulated matrix metalloproteinase-9 RNA expression in phorbol myristate acetate-stimulated T-cells. Co-culturing T-cells on transgenic ¢broblasts, expressing membrane-bound CD163, yielded no di¡erences compared to cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 22 publications
(23 reference statements)
5
65
0
1
Order By: Relevance
“…They include IL-1 ␣ , IL-1 receptor antagonist, IL-6, TNF ␣ , pulmonary and activation-regulated chemokine, and soluble IL-2 receptor ( 229-232 ). Such mediators clearly could play a role in disease progression (233)(234)(235). In ASM knockout mice, the majority of genes with elevated expression in lung and brain were those involved in the immune/ infl ammatory response ( 236 ).…”
Section: Infl Ammationmentioning
confidence: 99%
“…They include IL-1 ␣ , IL-1 receptor antagonist, IL-6, TNF ␣ , pulmonary and activation-regulated chemokine, and soluble IL-2 receptor ( 229-232 ). Such mediators clearly could play a role in disease progression (233)(234)(235). In ASM knockout mice, the majority of genes with elevated expression in lung and brain were those involved in the immune/ infl ammatory response ( 236 ).…”
Section: Infl Ammationmentioning
confidence: 99%
“…Also some reports show that CD163 soluble molecule may inhibit human T lymphocytes activation and proliferation in vitro (12,22), thereby facilitate suppression of the inflammatory response (5,22). Frigs and co-workers indicated that the soluble form of CD163 might have a direct suppressive action on CD4+ T helper cells (5).…”
Section: Functions Of Cd163 Scavenger Receptormentioning
confidence: 99%
“…Elevated plasma levels of sCD163 could be therefore a good indicator of an ongoing inflammatory or activation process of tissue macrophages. Besides, sCD163 appears to have immunosuppresive effects, inhibiting the activation and proliferation of T lymphocytes at concentrations not higher than physiological levels (Hogger and Sorg, 2001;Frings et al, 2002).…”
Section: Discussionmentioning
confidence: 99%